Risk and the construction of a European audit policy agenda: The case of auditor liability. (February 2015) - Samsonova-Taddei, Anna; Humphrey, Christopher
Abstract: In 2008, following a sustained policy campaign by the large international accounting firms, the European Commission issued a Recommendation that European Union (EU) Member States should limit civil liability for statutory auditors. The Recommendation, however, was far from the firms' desired outcome because, as a non-binding policy document, it left it to individual Member States to decide whether (or not) and how to limit auditors' liability exposure. This paper analyzes the European transnational audit policy-making processes by which such a decision was reached and what prevented the firms from securing a more definitive EU-wide policy solution with respect to auditor liability limitation. Drawing on Hilgartner's concept of a 'risk object', the paper reveals how a search for a policy consensus on auditor liability was invariably frustrated by the competing conceptualizations of, and exposure to, risk attributed to particular proposed liability arrangements. As such, auditor liability emerges as a constantly shifting regulatory construct rather than a dilemma waiting to be resolved. The study also emphasizes the residing significance of the authority of the nation state in the European audit policy context, with policy preferences of individual EU Member States having a substantial influence on the outputs of European audit policy making.